Effectiveness of Activated Carbon CaCl2 and NaNO3 Reducing Fatty Acids and Increasing the Quantity of Biodiesel Production - Muhali Muhali; Hendrawani Hendrawani; Baiq Mirawati; Hulyadi Hulyadi (Jurnal Penelitian Pendidikan IPA, 2023)
The study aims to identify the ability of carbon activated CaCl2 and NaNO3 in reducing fatty acids in jelah oil in biodiesel synthesis. This research is an experimental research with a quantitative descriptive approach. The variables measured in this study are the acidity level and quantity of biodiesel production from used cooking oil. The instruments used in this study include PH meters and Gas Cromatography mass Spectoscopy (GC-MS). The pH meter is used to measure the acid concentration of used cooking oil after going through a filtration process using activated carbon CaCl2, NaNO3, and inactivated carbon. The GC-MS instrument is used to identify the quantity of biodicell production made from used cooking oil. The data obtained are presented in the form of tables and graphs to identify the effect of the treatment given. Based on measurements of PH meters and GC-MS activated carbon CaCl2 is proven to be able to reduce fatty acids from an initial pH of 4 to 7 and get a biodicell of 100%. Based on these finding, it can be concluded that. Use of CaCl2 activated carbon has provev to be the most effective in reducing fatty acids and increasing the quantity of biodiesel production